Endocrine and Neuroendocrine Surgery - Howe, James R.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book brings together recognized experts in the field to describe their current techniques for the surgical treatment of diseased thyroid, parathyroid, and adrenal glands, as well as neuroendocrine tumors of small bowel, pancreas, liver, and skin. For each procedure, indications, operative steps, potential pitfalls and complications, and postoperative management are presented. The clear descriptions coupled with informative and beautiful illustrations will give the reader new perspectives and insights into the anatomy and conduct of these procedures. Endocrine surgery has been an area of special interest to surgeons for well over a century, while the increasing incidence of neuroendocrine tumors has more recently led to greater attention to these neoplasms. Significant advances have been made in a variety of areas, the most recent being the introduction of minimally invasive methods of removing diseased glands, and the improved understanding of the natural history of neuroendocrine tumors. .
PARATHYROID: Unilateral With Probe -- Unilateral Without Probe, Using PTH -- Subtotal Parathyroidectomy -- Total Parathyroidectomy With Autotransplantation -- Mediastinal/Thoracoscopic Approach -- THYROID: Thyroid Lobectomy And Total Thyroidectomy For Differentiated Cancer -- Total Thyroidectomy And Central Neck Dissection For MTC -- Substernal Goiter -- Modified Neck Dissection For Differentiated Thyroid Cancer -- ADRENAL: Open Approach -- Posterior Approach -- Transabdominal Laparoscopic -- Retroperitoneal Laparoscopic -- GI TRACT: Treatment Of Gastric And Duodenal Carcinoids -- Small Bowel Resection And Lymphadenectomy For Ileal Carcinoid -- Liver Debulking For NETs -- PANCREAS: Whipple -- Distal Pancreatectomy With/Without Splenectomy -- Laparoscopic Distal Pancreatectomy -- Enucleation For Neuroendocrine Tumors. OTHER NEUROENDOCRINE: Small bowel resection -- Liver surgery- Wide excision and sentinel node mapping for Merkel cell Carcinoma.
Keywords: Medicine; Endocrinology; Oncology; Minimally invasive surgery; Medicine & Public Health; Endocrinology; Oncology; Minimally invasive surgery